Assessing the impact of education in atrial fibrillation: A systematic review. (29th July 2021) - Cano Valls, A; Hendriks, JM; Sanders, P; Mont, LL; Gallagher, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Atrial Fibrillation (AF) is the most common heart rhythm disorder. Patient education is recommended as part of comprehensive AF management. Despite this the impact of education alone on outcomes in AF populations is unknown. Purpose: The aim of this study was to describe the impact of education on clinically relevant outcomes in patient with AF including mortality, hospital admissions, emergency department presentations, stroke and quality of life.  Methods: The authors searched Pubmed, Embase, CINAHL, Cochrane database and Psycinfo from inception until September 2019. Studies were included if they were prospective and of randomized controlled or observational design with a minimum follow-up 3 months and published in English. Results: A total of 1667 studies were screened with 37 undergoing full text review and 6 meeting eligibility criteria. There was a total of 588 participants with a mean age of 65.63 ± 11.05 and 60.71% were male. A meta-analysis was unable to be performed due to heterogeneity in reporting of outcomes. Two studies examined the impact of education on mortality with no impact evident from either intervention. The impact of education on hospitalisations (all cause – 3 studies, cardiovascular – 1 study and AF - 2 studies) was explored in five studies with no impact on this outcome from any intervention. Similarly, there was no impact of education on emergency department presentations, except for one study in which a video was used in addition to standardised education. There was no impact on stroke from two studies exploring this outcome. There was no evidence of impact of education on general or AF specific quality of life. Conclusions: There is little evidence to suggest that educational interventions to date have significantly impacted on death, hospitalisations, emergency department presentations or quality of life in AF populations. There is an urgent need to identify optimal modes and components of educational interventions to improve patient outcomes and reduce health care burden in AF.